An Analysis of Grammatical Errors in Writing Recount Text at the Eighth Grade of SMP Negeri 20 Kota Jambi - Selvia Lisa Asni; Susi Susanti (International Journal of Language Teaching and Education, 2018)
This study aims to analyze and classify the types or mistakes of students using simple past tense in writing text recount. In addition, this study also aims to determine the cause of errors made by the students using simple past tense in writing text recount, This research used qualitative methods. Meanwhile, the research design used is case study. Furthermore, the writer chose the 8th grade students and observed 26 students. The writer used a written test and interviews to gain the data from some students and an English teacher. Based on this research, it is found that students do all kinds of errors (omission, addition, selection and misordering). The type of error most often done by the students was omission error with 166 errors or 38.97%. The second position was a selection error with 162 errors or 38.03%. The third position was the addition error with 67 errors or 15.73%. Then the last position was misordering error with 31 errors or 7.28%. In addition, the errors were caused by the complexity of the English system itself and not because of the influence of the Indonesian system (intralingual transfer). Moreover, students lacked of understanding of the grammar that became the cause of the error. In this study, most students did not understand verb 1,2,3 as well as the proper use if “be” in a sentence. This suggested that students had difficulty with the use of grammar in writing